Microwave Absorption Properties of Graphene Oxide Derived from Coconut Shell Waste by Modified Hummer's Method - Nadia Ardianti; Yenni Darvina; Fadhila Ulfa Jhora; - Ramli (Department of Physics – Universitas Negeri Padang UNP, 2022)
Coconut shells are organic waste, so they can be used as an alternative for carbon source. In this study, the synthesis of graphene oxide (GO) from coconut shell waste will be carried out. The results of the synthesis of GO will then be tested for microwave absorbing properties because it can be applied in various fields, such as information technology, medical equipment, industry, polymer synthesis, and organic synthesis. GO synthesis was carried out using the modified Hummers method. There are several stages in this study, namely the stage of preparing old coconut shells, the stage of carbon activation, the stage of GO synthesis, and the stage of sonication and neutralization of GO. The coconut shell was treated with variations in the sintering temperature to see its effect on the microwave absorbing properties. The sintering temperatures used in this study were 250°C, 300°C, 350°C, 400°C, and 450°C. GO characterization was carried out using X-Ray Diffraction (XRD), Fourier Transform Infra-Red (FTIR), and Vector Network Analyzer (VNA) to determine the phase, functional groups, and microwave absorption properties of GO. In the results of GO characterization using VNA, it was found that there was an effect of temperature variations. GO can be synthesized from old coconut shell waste using the modified Hummers method and has a GO phase result. The best microwave absorbing properties are at a sintering temperature of 400°C with a reflection loss value of -24.40 dB. Absorbing coefficient 93.97% at 10.40 GHz